Estudio de la práctica de valores de paz en la cultura corporativa y espacios informativos de los canales de televisión de la ciudad de Loja, en el período 2019. - Obaco Obaco, Tanya Veronica (2020)
This research work is directed by the television channels of the city of Loja: Ecotel TV, UV Televisión, Canal Sur and Plus TV. The general objective is focused on studying the practice of peace values in corporate culture and informative spaces of the television channels of the city of Loja in the period 2019. For this purpose, the relationship between the values of peace and the different information transmitted in the news programs of each television channel was analyzed, with the application of the composed week. A total of five weeks were analyzed from the month of July to December 2019, for which a content card was prepared that compiled the pieces of each news program, fixing the existing amount of them, the content, the schedule, the location per block, the geographical location, detailing the number and type of sources used, determining what value it is related to, positive and negative aspects of the value and in addition to the fact, and finally, observing the approach they emit. The research shows that the practice of peace values does take place, but not in a constant or fixed way, because the television media do not know the principles immersed in the culture of peace and do not appear as part of their corporate culture, although there is an application of universal values. Within the five weeks studied, a total of 75 pieces were found distributed among the four channels, which reflects a minuscule contribution to the promotion and practice of the culture of peace in the local media news. In view of the minuscule knowledge about the values of peace, a planning guide for the use and practice of these values in the internal part of the channels and in the content disseminated through the news